2019
DOI: 10.1016/j.cej.2019.121978
|View full text |Cite
|
Sign up to set email alerts
|

Tuning electronic and composition effects in ruthenium-copper alloy nanoparticles anchored on carbon nanofibers for rechargeable Li-CO2 batteries

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 65 publications
1
41
0
Order By: Relevance
“…In a cathodic scan, due to the electrochemical reduction of CO 2 , a conspicuous cathodic peak evolves and consecutively gains intensity. [33] For the subsequent anodic scan, an anodic peak starting from 2.8 V (4e…”
Section: Resultsmentioning
confidence: 99%
“…In a cathodic scan, due to the electrochemical reduction of CO 2 , a conspicuous cathodic peak evolves and consecutively gains intensity. [33] For the subsequent anodic scan, an anodic peak starting from 2.8 V (4e…”
Section: Resultsmentioning
confidence: 99%
“…Jin et al fabricated an intermixed composite catalyst by anchoring Ru–Cu alloy on CNF (RuCu/CNFs). [ 79 ] Li–CO 2 cells with the RuCu/CNF catalyst showed an extremely stable cycling performance (without an obvious capacity decline for 110 cycles). This research demonstrated that alloying a second metal to a noble metal would be a promising approach for developing CO 2 electrocatalysts.…”
Section: Cathode Materials and Electrocatalysts For Li–co2 Batteriesmentioning
confidence: 99%
“…This research demonstrated that alloying a second metal to a noble metal would be a promising approach for developing CO 2 electrocatalysts. [ 79 ] Zhang et al developed a composite catalyst with Ru–Cu particles codispersed on a graphene substrate. [ 80 ] They claimed that the synergistic effect of Cu and Ru could control the growth of discharge products (Figure 5d).…”
Section: Cathode Materials and Electrocatalysts For Li–co2 Batteriesmentioning
confidence: 99%
“…For example, Ru nanoparticles on C nanofibers (CNFs) display a low overpotential of 1.43 V after 50 cycles at 100 mA g −1 in Li-CO 2 batteries [22]. Jin et al [23] reported that intermixed RuCu alloy nanoparticles on CNFs can work steadily for 110 cycles in Li-CO 2 batteries. Although these metal nanoparticle catalysts have improved the performance of Li-CO 2 batteries to some extent, the aggregation of nanoparticles and limited active sites of metal catalysts are obstacles preventing further improvement in the reversible decomposition of Li 2 CO 3 /C.…”
Section: Introductionmentioning
confidence: 99%